THE INFLUENCE OF THE IMPLEMENTATION OF STORYTELLING ON THE IMPACT OF HOSPITALIZATION ON PRESCHOOL-AGE CHILDREN AT MUHAMMAD SANI KARIMUN HOSPITAL - Fithri, Novia Ramadhani; Pramadhani, Wulan; Utami, Rizki Sari Utami; Murniasih, Elvi; Purnamasari, Indah (Journal of Nursing Periodic, 2025)
Introduction: Children who are hospitalized are trying to adapt to the new environment in the hospital, being separated from their parents so that this condition can cause stress in the child. Method: The method used in this research is a pre-experimental design, Pretest and Posttest Without Control Group, using purposive sampling with a total of 30 respondents. Statistical tests in this study used Wilcoxon. Results: The results of the research after storytelling had a p-value of 0.000 < 0.005, which means that Ho was rejected and Ha was accepted, so it can be concluded that there is an influence between storytelling and inpatient stress in early childhood. Conclusion: It is hoped that surgery can be applied as a method to provide comfort to children of gestational age who are hospitalized so that they are not stressed.